2019
DOI: 10.21560/spcd.v19i49119.487325
|View full text |Cite
|
Sign up to set email alerts
|

Türk Toplumunda Suri̇yeli̇lere Yöneli̇k Algilanan Tehdi̇tler Ve Çözüm Öneri̇leri̇

Abstract: With the out break of Syrian war, the number of refugees seeking asylum in another country worldwide has increased sharply. As a result of the Turkey's open border policy, Turkey has came one of the most affected countries by the crisis, and become the most Syrians hosted country. At the beginning of the Syrian influx, the attitudes of Turkish society towards Syrians were positive based on the understanding of hospitality. However, with the increase in the number of Syrians and the length of their stay, Turks'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 28 publications
(39 reference statements)
0
5
0
8
Order By: Relevance
“…Bu bağlamada araştırma kapsamında dil sorunları, üzerinde durulan en önemli kültürel sorundur. Göçmenlerin hem kendi aralarında hem de ev sahibi toplumdaki insanlarla sosyal ilişki ve Benzer biçimde başka araştırmalarda da Suriyeliler son zamanlarda yaşadıkları ötekileştirilme veya dışlanmalarının nedenini milliyetiliğin artmasına bağlamışlardır (Akkır, 2019;Ekici, 2019). Suriyeliler gündelik hayatta ırkçılığa ve ayrımcılığa maruz kaldıkları ve vatan haini olarak nitelendirildikleri için kendilerini güvende hissetmemektedirler (Şimşek, 2017).…”
Section: Kültürel Sorunlara İlişkin Bulgularunclassified
See 1 more Smart Citation
“…Bu bağlamada araştırma kapsamında dil sorunları, üzerinde durulan en önemli kültürel sorundur. Göçmenlerin hem kendi aralarında hem de ev sahibi toplumdaki insanlarla sosyal ilişki ve Benzer biçimde başka araştırmalarda da Suriyeliler son zamanlarda yaşadıkları ötekileştirilme veya dışlanmalarının nedenini milliyetiliğin artmasına bağlamışlardır (Akkır, 2019;Ekici, 2019). Suriyeliler gündelik hayatta ırkçılığa ve ayrımcılığa maruz kaldıkları ve vatan haini olarak nitelendirildikleri için kendilerini güvende hissetmemektedirler (Şimşek, 2017).…”
Section: Kültürel Sorunlara İlişkin Bulgularunclassified
“…Bu durum sonucu pek çok göçmen gibi eğitim düzeyi yüksek Suriyeliler de ucuz işgücü olarak yasadışı ve düşük ücretle çalıştırılmakta ve yerel halkta düşük ücretle çalışmalarından dolayı tepki görmektedirler. Diğer illerde yapılan bir çok araştırmada(Aydın & Durgun, 2018; Çağlar-Deniz vd., 2016;Ekici, 2019; Morgül vd., 2021;Tanrıverdi & Ulu, 2020) Suriyelilerin ekonomik olarak bir yük ve bir tehdit olarak algılandıkları ve bu nedenle sıklıklıkla ayrımcılığa maruz kaldıklarını sonucuna ulaşılmıştır. Eğitim düzeyi yüksek Suriyelilerin, Türk işçilerin kendilerini düşük ücret aldıkları için çalıştırdıklarının ve eşit işe eşit ücret almadıklarının farkında oldukları anlaşılmaktadır.…”
unclassified
“…A study by Gozubuyuk et al (2019) found that Turkish people have many different, inaccurate and exaggerated opinions about Syrian refugees and that there is a lack of reliable information regarding legal arrangements and rights granted to them. Turkish people consider Syrian refugees a threat to cultural structure, social and moral order, economic order, security and access to basic services (Ekici, 2019). Ersoy (2019) concluded that local community viewed Syrian refugees a security threat and linked the rise in social problems to the presence of refugees.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the factors underlying the reactive approach of the local population towards the Syrian refugees is the problems stemming from different languages, cultures and lifestyles (Oytun and Gündoğar, 2015). The cultural differences of Syrians, in particular, lead local people to think that immigrants will experience difficulties in adapting to Turkish society (Ekici, 2019).…”
Section: Introductionmentioning
confidence: 99%